Genetic Variants Influencing Spironolactone Effectiveness: A Pharmacogenomic Perspective - Amukti, Danang Prasetyaning; Pratami, Ria Indah; Ananda, RA Dewinta Sukma (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2026)
Background: Spironolactone, a mineralocorticoid receptor antagonist, is widely used to treat resistant hypertension, heart failure, and primary aldosteronism. However, significant interindividual variability in therapeutic response suggests a genetic contribution to its effectiveness. Method: This study employed a bioinformatics approach using secondary data from PharmGKB, GTEx Portal, and HaploReg v4.2 to identify genetic variants and gene expression profiles potentially influencing spironolactone response. Result: Seven variants were identified as associated with spironolactone effectiveness: rs1799752 (ACE), rs3890011 and rs1126742 (CYP4A11), rs1801253 (ADRB1), rs1799983 (NOS3), rs4961 (ADD1), and rs1042713 (ADRB2). Tissue-specific expression analysis showed ACE highly expressed in testis, CYP4A11 in liver, ADRB1 in lung, NOS3 in spleen, ADD1 in tibial artery, and ADRB2 in skin. Functional predictions indicated that missense variants (rs1126742, rs1799983, rs4961) may affect protein structure, while intronic variants (rs1799752, rs3890011) may influence gene regulation. Conclusion: These findings suggest that pharmacogenomic profiling may help predict spironolactone response and support the development of personalized treatment strategies. Further clinical validation is required to establish the therapeutic relevance of these variants